Investigating housing preferences after covid-19 pandemic in Malaysia - Ong, Hoo Yee (2022)
COVID-19 pandemic has brought about profound changes in human social and health related behaviour. The new norm led to a shift in housing preferences as building occupants spent more time at home than previously. Numerous studies were conducted on housing preferences in Malaysia before the outbreak. However, limited studies were dedicated to housing preferences in the pandemic context. Therefore, this study aims to uncover the housing preferences after the COVID-19 pandemic in Malaysia. The objectives of this study are to identify post-COVID-19 housing preferences in Malaysia, to evaluate the importance level of post-COVID-19 housing preferences in Malaysia and to investigate the influence of social demographics on post-COVID-19 housing preferences in Malaysia. The identified fifty-one postCOVID-19 housing preferences were important to homebuyers in purchasing a home and categorised into eight parameters, which are financial, locational, physical, structural and equipment, spatial arrangement, health and comfort, green and technological. A quantitative approach was adopted for this study. Online and handdelivered questionnaires were distributed to homebuyers in Klang Valley and 141 responses were collected. Data obtained were then analysed by Cronbach Alpha Reliability Test, Friedman Test, Mann-Whitney U Test, and Kruskal-Wallis. The results discovered that homebuyers would most prioritise health and comfort parameters after the pandemic. Besides, homebuyers with distinct gender, ages, ethnicity, marital status, household size, educational level and income levels have different preferences in purchasing a home. The findings of the research are useful to the property and the housing industry in understanding the latest demand and trends from the perspective of homebuyers after the COVID-19 pandemic.